Occupation growth, skill prices, and wage inequality - Michael Böhm; Hans-Martin von Gaudecker; Felix Schran (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper studies the relationship between occupational employment, occupational wages, and rising wage inequality. We document that in all occupations, entrants and leavers earn less than stayers. This suggests selection effects that are negative for growing occupations and positive for shrinking ones. We estimate a model of occupational prices and skills, which includes occupation-specific skill accumulation and endogenous switching across many occupations. Consistent with leading explanations for occupational changes, estimated prices (i.e., selection-corrected wages) and occupational employment growth are positively related. Just over 40% of selection is due to age in the sense that marginal workers have had less time to accumulate skills. The remainder is due to Roy-type selection, i.e., workers reacting to changing prices and shocks unrelated to age. Skill prices establish a long-suspected quantitative connection between occupational changes and the surge in wage inequality.
Keywords: J21; J23; J24; J31; 330; Skill Prices; Selection Effects; Multidimensional Skill Accumulation; Occupational Employment and Wages; Administrative Panel Data; Wage Inequality